The Fukushima Nuclear Accident and Environmental Risk: A Survey of Fukushima Residents - Takeshi Miyawaki; Shinya Sasaoka (Asian Journal for Public Opinion Research, 2017)
The Fukushima nuclear accident caused by an earthquake and a subsequent tsunami on March 11, 2011 has seriously impacted the environment surrounding the Fukushima Daiichi nuclear power plant. While all the residents near the plant were evacuated from the area deemed uninhabitable after the accident, residents of the neighboring area outside of the evacuation zone still seem to live in fear of invisible radiation. To understand Fukushima residents’ thinking about the environmental risks that accompany a nuclear disaster, we utilize a poll of the residents of Fukushima conducted in 2013. Based on the survey data, we reveal factors that seem to strongly affect their knowledge and concerns about nuclear power plants. The results of the multivariate analysis show the importance of the following two factors: (1) confidence in mass media, and (2) trust in institutions in charge of administering the accident, especially the central government, the Nuclear and Industrial Safety Agency, and Tokyo Electric Power Company. We conclude that the more people trust mass media and particular institutions, the more likely it is that they are have an elevated sense of anxiety and fear of the presence of nuclear plants.